2013
DOI: 10.5539/elt.v6n12p167
|View full text |Cite
|
Sign up to set email alerts
|

A Corpus-Based Study on English Prepositions of Place, in and on

Abstract: This corpus-based study examined the usage, mastery and developmental pattern (Norwati, 2004) of English prepositions of place, in and on across three different academic levels namely Form 4, Form 5 and College students. The Malaysian Corpus of Students Argumentative Writing (MCSAW) was used as the source of data in analyzing the use of prepositions of place, in and on in the students' argumentative essays. In achieving this, the concordance output was utilized to determine the frequency and types of errors ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 4 publications
0
4
1
1
Order By: Relevance
“…The use of questioning strategy assisted learners to master English prepositions of movement. The finding was incongruent with what, Arjan et al (2013) posited that it is difficult for foreign language learners to master the use of English prepositions of movement correctly.…”
Section: 1analysis Of Data From Teaching Observationscontrasting
confidence: 69%
See 1 more Smart Citation
“…The use of questioning strategy assisted learners to master English prepositions of movement. The finding was incongruent with what, Arjan et al (2013) posited that it is difficult for foreign language learners to master the use of English prepositions of movement correctly.…”
Section: 1analysis Of Data From Teaching Observationscontrasting
confidence: 69%
“…Teaching technique and language use within the classroom environment is, in this regard, seen in terms of the need to communicate meaning to ensure access to knowledge of English prepositions and thereby foster individual development (Cleghorn & Rollnick, 2002). Arjan, Abdullah and Roslim (2013) indicate that it is difficult for foreign language learners to master the use of English prepositions correctly as many English prepositions have several different functions. In addition, Lorintz and Gordon's (2012) English prepositions are very difficult for English language learners to master due to the sheer number of them in the English language and their polysemous nature.…”
Section: Use Of Question-and-answer Methods In Teaching English Prepo...mentioning
confidence: 99%
“…Looking at the problems in using the prepositions which are shown in the previous studies (Arjan, Abdullah, & Roslim, 2013;Huang, 2010;Johanson, 2017;Loke et al, 2013;Mahmoodzadeh, 2012;Saravanan, 2014;Sudhakaran, 2015;Viloria, Ruiz, & Sanchez, 2017), the students tend to misuse the prepositions. From those misuses, Bram (2005); Chodorow, Tetreault, and Han (2007); and Jha (1991) categorized them into three types of preposition misuses:…”
Section: Problems Of Using English Prepositionsmentioning
confidence: 89%
“…In Malaysia, the students have difficulties in using prepositions on and at to indicate the time (Loke et al, 2013). Another study showed how Malaysian students also expesaga, Vol 2(1), February 2021 rienced difficulties in using prepositions of place, in and on (Arjan, Abdullah, & Roslim, 2013). All of them still look at how important the use of prepositions in writing is.…”
Section: Problems Of Using English Prepositionsmentioning
confidence: 99%
“…Permasalahan ini juga ditemukan dalam penelitian sebelumnya. Siswa merasa bingung dalam menggunakan preposisi in dan on serta mereka tidak mengalami perkembangan yang signifikan dari satu jenjang pendidikan ke satu jenjang yang lain yang lebih tinggi (Arjan;Roslim, 2013). Hal serupa juga terjadi pada penutur asli Bahasa Arab yang menghasilkan beragam kesalahan dalam penggunaan preposisi.…”
Section: Persepsi Mahasiswa Terhadap Pemanfaatan Video Onlineunclassified